Developing A Self-Protection Guidebook for Kindergarten Teachers - Oktavianingsih, Eka; Ayriza, Yulia (Indonesian Journal of Early Childhood Education Studies, 2018)
This study aims to (1) develop a self-protection learning guidebook for kindergarten teachers, (2) test the feasibility of guidebooks based on aspects of validity and practicality, and (3) revise the book based on the feasibility test results. This research was a development research using Borg & Gall (1983) development model. The subjects of this research are kindergarten teachers working with children aged 5-6 years old in Sanden, Bantul, with various demographic characteristics. The eligibility of the guidebooks was obtained from the aspects of the validity from the assessment of material experts and media experts in the field, while the practicality aspect was obtained from the questionnaire by the users, i.e the teachers. The results showed that the guide books has met the aspects of validity and practicality.